Implementasi manajemen diri dalam perilaku ekonomi konsumen muda: Studi kasus pengelolaan keuangan pribadi mahasiswa UIN Malang - Putri, Rosyadah Rensy Dwi Murnisa (Maliki Interdisciplinary Journal, 2026)
This study aims to analyze in depth the implementation of self-management and its important role in shaping the economic behavior of young consumers, particularly among students at the State Islamic University of Maulana Malik Ibrahim Malang, specifically in personal financial management. Self- management is a process of self-control that encompasses intellectual, emotional, spiritual, and physical aspects, focusing on discipline. This discipline helps students avoid impulsive spending. Effective self- management practices are seen in personal financial management that includes wise use of funds, identification of funding sources, risk management, and future financial planning. Based on the results of the study, it was found that effective self-management practices are manifested in systematic personal financial management, covering four main areas: wise use of funds (proportional allocation), identification and utilization of funding sources, risk management (through emergency funds/insurance), and long-term financial planning for the future. Students who implement strong self-management tend to be rational, independent, and future-oriented consumers, rather than becoming impulsive consumers who are financially vulnerable. Therefore, this study suggests that educational institutions and the environment play an active role in strengthening self-management through financial training programs and character development, as well as improving students’ financial literacy.